Phytotherapy in endodontics - Benetti, Francine [UNESP]; dos Reis-Prado, Alexandre Henrique; Nunes, Gabriel Pereira [UNESP]; Cosme-Silva, Leopoldo; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
Studies of the herbal therapies applicability in dentistry field increase prevention and treatment of several diseases. The natural products show anti-inflammatory, antioxidant, and antimicrobial properties. According to the World Health Organization, phytotherapy is the use of herbal substances with therapeutic values, involving minimal or no industrial processing. Some endodontic materials may cause defects on the dentin and/or being an irritant to the tissues, besides of limited antimicrobial effectiveness. The herbal alternatives can prevent adverse effects of synthetic drugs as toxicity and microbial resistance. In addition, herbal products include cost-effectiveness, increase quality of life, nutritional values, easy availability and increased service life. This chapter will present studies of the several herbal alternatives with different potential in endodontic applications: irrigating solutions, intracanal medication, addition in endodontic sealer and for repair materials, and other applications.
Keywords: Bioactive Materials; Dentin; Enamel; Remineralization; Teeth Hard Tissues